A Mathematical Walk into the Paradox of Bloch Oscillations. Issue 5 (29th July 2021) - Barletti, Luigi
Abstract: We mathematically describe the apparently paradoxical phenomenon that the electric current in a semiconductor can flow because of collisions, and not despite them. A model of charge transport in a one-dimensional semiconductor crystal is considered, where each electron follows the periodic Hamiltonian trajectories, determined by the semiconductor band structure, and undergoes non-elastic collisions with a phonon bath. Starting from the detailed phase-space model, a closed system of ODEs is obtained for averaged quantities. Such a simplified model is nevertheless capable of describing transient Bloch oscillations, their damping and the consequent onset of a steady current flow, which is in good agreement with the available experimental data.